American Telemedicine Association: Annual International Meeting & Tradeshow - Bernard, Jordana (International Journal of Telerehabilitation, 2015)
The 2016 American Telemedicine Association (ATA 2016) Annual International Meeting & Tradeshow, will be held May 14-17, 2016 at the Minneapolis Convention Center, Minneapolis, MN.